2014
DOI: 10.1093/jxb/eru200
|View full text |Cite
|
Sign up to set email alerts
|

Cell-autonomous-like silencing of GFP-partitioned transgenic Nicotiana benthamiana

Abstract: We previously reported the novel partitioning of regional GFP-silencing on leaves of 35S-GFP transgenic plants, coining the term "partitioned silencing". We set out to delineate the mechanism of partitioned silencing. Here, we report that the partitioned plants were hemizygous for the transgene, possessing two direct-repeat copies of 35S-GFP. The detection of both siRNA expression (21 and 24 nt) and DNA methylation enrichment specifically at silenced regions indicated that both post-transcriptional gene silenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…(Voinnet et al ; Tournier et al ; Molnar et al ; Bai et al ). While unidirectionality (Palauqui et al ; Sohn et al ) or directionality‐depended efficiency of silencing spread (Molnar et al ) have been reported, other factors might have an impact on the silencing spread efficiency, such as the age or the developmental stage of the plants (Liang et al ), or the grafting method (Crete et al ).…”
Section: Identity and Movement Of The Mobile Signalmentioning
confidence: 99%
“…(Voinnet et al ; Tournier et al ; Molnar et al ; Bai et al ). While unidirectionality (Palauqui et al ; Sohn et al ) or directionality‐depended efficiency of silencing spread (Molnar et al ) have been reported, other factors might have an impact on the silencing spread efficiency, such as the age or the developmental stage of the plants (Liang et al ), or the grafting method (Crete et al ).…”
Section: Identity and Movement Of The Mobile Signalmentioning
confidence: 99%
“…Sohn et al 58 published a whole transcriptome analysis in silenced and non-silenced leaf regions of a N. benthamiana transgenic line exhibiting local cell-autonomous leaf-partitioned GFP silencing achieved through both PTGS and TGS mechanisms. In this study, leaf region-specific DEGs were three times more abundant in non-silenced than in silenced regions.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic GFP-PTGS incurs changes in whole transcriptome pro les Sohn and colleagues (2014) 59 published a whole transcriptome analysis in silenced and non-silenced leaf regions of a N. benthamiana transgenic line exhibiting local cell-autonomous leaf-partitioned GFP silencing achieved through both PTGS and TGS mechanisms. In this study, leaf region-speci c DEGs were three times more abundant in non-silenced than in silenced regions.…”
Section: Discussionmentioning
confidence: 99%